Pelatihan Pengembangan Kapasitas Organisasi Desa Wisata Sukarame untuk Mendukung Program Geowisata di Kabupaten Pandeglang - Jamilah Mihardja, Eli; Lucyanda, Jurica; Arni Widyastuti, Dominica; Fajrin Ismail, Rexy; Azzura, Denisa (LPkM Universitas Bakrie, 2024)
The purpose of this activity is to develop the organizational capacity of Sukarame Tourism Village as a geo-tourism program in Pandeglang Regency. The activity was carried out with partners, namely the Pandeglang Regency Tourism Office and the Ujung Kulon Geopark Management Agency. Sukarame Tourism Village has achieved achievements as one of the best tourist villages in Indonesia. However, as one of the areas in the Ujung Kulon Geopark area, tourism village organizations still experience limited literacy related to branding strategies, promotion and marketing, and financial management. The method of community service is training and mentoring to design and implement geo-tourism promotion and financial management by optimizing the use of media. Training activities in the form of material presentation and discussion related to branding strategies, promotion and marketing, and financial management. While mentoring activities in the form of helping participants create social media for their business promotion. The results of the activity concluded that there was an increase in knowledge and understanding of branding, promotion and marketing strategies, and simple financial management according to accounting standards. The increase was seen from the results of the pre-test and post-test, there was an increase in participants' understanding related to financial management and reporting above 80%; understanding related to promotion and marketing above 12%; and understanding related to the importance of media in promotion and marketing as much as 88%. This activity provides other outputs such as content uploaded on social media, documentaries, and special websites for the development of geotourism programs.